2020
DOI: 10.1101/2020.10.02.20205567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of pathogen reduction methods on immunological properties of the COVID-19 convalescent plasma

Abstract: Background and Objectives In the absence of a vaccine or specific antiviral drugs against SARS-CoV-2 COVID-19 convalescent plasma became one of the experimental treatment options in many countries. Aim of this study was to assess the impact of different pathogen reduction technologies on the immunological properties of COVID-19 convalescent plasma. Materials and Methods In our experiment 140 doses of plasma collected by plasmapheresis from COVID-19 convalescent donors were subjected to pathogen reduction with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Methylene blue is a method of pathogen inactivation for plasma that is widely used in some countries in Europe. A study from Russia showed that some units of plasma lost neutralising activity with methylene blue inactivation, 34 whereas other studies found no difference. 35,36 We analysed the neutralising activity of stored donor samples (ie, before methylene blue treatment) compared with the plasma unit (ie, after methylene blue treatment) in a subgroup of plasma units and we found no differences in neutralising antibody titres (median ID50 1:1256 [IQR 1:709-1:2712] vs 1:1287 [1:349-1:3333]; p=0•32).…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue is a method of pathogen inactivation for plasma that is widely used in some countries in Europe. A study from Russia showed that some units of plasma lost neutralising activity with methylene blue inactivation, 34 whereas other studies found no difference. 35,36 We analysed the neutralising activity of stored donor samples (ie, before methylene blue treatment) compared with the plasma unit (ie, after methylene blue treatment) in a subgroup of plasma units and we found no differences in neutralising antibody titres (median ID50 1:1256 [IQR 1:709-1:2712] vs 1:1287 [1:349-1:3333]; p=0•32).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that photoinactivation with methylene blue does not significantly reduce the titers of SARS-CoV-2 antibodies. [36][37] In fact, the methylene blue method has been reported to be less detrimental to anti-SARS-CoV2-2 titers than other pathogen-reduction technologies currently applied to donated plasma. 36 However, we cannot certainly disregard some decrease in the in vivo neutralizing capacity due to pathogen-reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Donor CCP was submitted to pathogen‐reduction to minimize the hypothetical risk of SARS‐CoV‐2 transmission and comply with the Spanish Government requirements for plasma transfusion. Prior studies have shown that photoinactivation with methylene blue does not significantly reduce the titers of SARS‐CoV‐2 antibodies 36–37 . In fact, the methylene blue method has been reported to be less detrimental to anti‐SARS‐CoV2‐2 titers than other pathogen‐reduction technologies currently applied to donated plasma 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with the aforementioned findings, heparan sulfatehas been recognized as an important attachment factor for SARS-CoV-2 infection in human lung damage, hyper-inflammatory reaction, etc (Pardo Andreu, 2021). Moreover, MB has other potential applications in the COVID-19 pandemic, including decontamination of personal protective equipment (Lendvay et al, 2021), and pathogen reduction of COVID-19 convalescent plasma (Kostin et al, 2021). Additionally, some studies suggest the prospective use of photodynamic therapy as an effective method for the prevention and treatment of COVID-19 (Svyatchenko et al, 2021).…”
Section: Interactions Between Heparan Sulfate and Sars-cov-2 Spike Proteinmentioning
confidence: 99%